Polymer composition containing pea starch

By using the ratio of high content pea starch and aliphatic-aromatic copolyester in the polymer composition, the mechanical properties and biodegradability of the garbage bag and transportation bag films are improved, and the performance deficiency in the prior art and Non-biodegradable problem.

CN116745362BActive Publication Date: 2025-01-03BIONATURAL PACKAGING MATERIALS RES & DEV GMBH & CO KG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280011663.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-01-25
Filing Date
2022-01-25
Publication Date
2025-01-03
Estimated Expiration
2042-01-25

Smart Images

  • Figure CN116745362B_ABST
    Figure CN116745362B_ABST
Patent Text Reader

Abstract

The present invention relates to a polymer composition, which contains at least 25.5% to 50% by weight of starch and 30% to 74.5% by weight of aliphatic-aromatic copolyesters, respectively, based on the total dry weight of the polymer composition, characterized in that the starch contains at least 25% by weight of pea starch, based on the total dry weight of the starch. The present invention also relates to a method for preparing the polymer composition according to the present invention and a molded part, film or fiber containing the polymer composition according to the present invention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymer composition, a method for preparing a polymer composition, the use of a polymer composition and a molded article, a film or a fiber comprising the polymer composition. Background Art

[0002] Plastics are materials consisting of macromolecules. Their versatility and technical properties such as formability, elasticity, breaking strength and stability make them suitable for a wide range of applications. Depending on the application, the mechanical requirements placed on plastics are very different. When using plastics in transport bags, for example, high tensile strength, high tear elongation, high tear propagation resistance and high dart drop values ​​are desirable for the plastic films used.

[0003] Conventional plastics have many undesirable properties: their production consumes large amounts of fossil resources such as oil and gas, many of them are non- or barely-biodegradable, and their CO2 balance is often very poor. In order to reduce the consumption of fossil resources and achieve a better CO2 balance, in recent years more and more plastics have been produced from renewable raw materials such as plants. Polymers that are based at least partly or completely on renewable raw materials are also called "biobased" polymers.

[0004] Many plastics are very durable and degrade very slowly in nature, some over decades to centuries. In view of current environmental developments, such as litter in the oceans, there is an increased demand for biodegradable plastics, i.e. plastics that can be broken down by enzymes of naturally occurring microorganisms such as fungi or bacteria. The biodegradability of a plastic depends entirely on the chemical structure of the plastic and its ability to be converted into natural metabolic end products through biological activity. Therefore, bio-based plastics are not necessarily biodegradable.

[0005] Biodegradable polymer compositions are mainly used in the packaging and catering sectors. In addition, they are also used in agriculture and horticulture as well as in the pharmaceutical and medical sectors. Biodegradable polymer compositions are particularly suitable for the production of garbage bags, transport bags, disposable tableware (cups without handles, cups with handles, plates, cutlery), packaging films, bottles, fruit and vegetable trays (so-called trays), packaging aids (loose filling crumbs), covering films, flower pots, etc.

[0006] Particularly in the field of garbage bags and transport bags, particularly high mechanical requirements are placed on plastic films produced from polymer compositions with regard to tear resistance and load-bearing capacity.

[0007] For these reasons, there is a particular demand for plastics which have good mechanical properties and which are at the same time at least partly biobased and / or biodegradable.

[0008] Polymer compositions for producing such plastics based on starch and aliphatic-aromatic copolyesters are known from the prior art.

[0009] For example, thermoplastic polymer compositions based on potato starch without plasticizers are available under the trade name GF 106 / 02 is commercially available from BIOTEC GmbH & Co. KG, Emmerich (Germany), and is a polymer composition particularly suitable for blown film extrusion, flat film extrusion and injection molding of biodegradable products.

[0010] The preparation and properties of plasticizer-free thermoplastic polymer blends based on starch and aliphatic-aromatic copolyesters are described, for example, in the publication EP 0 596 437 B1.

[0011] As stated in Handbook of Biodegradable Polymers, 2nd edition, Smithers Rapra Technology, 2014, p. 265, common and most important sources of starch are agricultural crops such as corn, wheat, potato, cassava and rice.

[0012] WO 2005 / 120808 A1 describes a method for producing a biodegradable plastic film, comprising producing a biodegradable blown film and subsequent uniaxial or biaxial cold stretching. The biodegradable polymer used can be an aliphatic-aromatic copolyester, such as polybutylene adipate / terephthalate. Diesters Furthermore, the polymer composition employed may contain starch.

[0013] A disadvantage of the polymer compositions known from the prior art is that the mechanical properties of the molded parts, films and fibers produced therefrom need to be improved or that these polymer compositions are not or only to a small extent biobased and / or are not or only slowly and incompletely biodegradable. Summary of the invention

[0014] The object of the present invention is to provide a polymer composition which at least partially overcomes one or more disadvantages of the prior art. For this purpose, the polymer composition should provide molded parts, films and fibers produced therefrom with excellent mechanical properties, which are at least partially bio-based and / or biodegradable. The polymer composition should be particularly suitable for producing particularly stable and load-bearing garbage bags and transport bags. In particular, films produced from the polymer composition should have high tensile strength, high tear elongation, high tear propagation resistance and high dart drop values.

[0015] Another object of the present invention is to provide a method by which such a polymer composition can be prepared. The method should in particular be rapid and efficient.

[0016] All or some of these objects are achieved according to the invention by the polymer composition according to claim 1 , the method according to claim 14 , the polymer composition according to claim 20 , the use according to claim 21 , and the shaped article, film or fiber according to claim 22 .

[0017] Advantageous embodiments of the invention are given in the dependent claims and are explained in detail below.

[0018] The present invention provides a polymer composition, which contains at least the following components, respectively, relative to the total dry weight of the polymer composition: a) 25.5 wt % to 50 wt % of starch, b) 30 wt % to 74.5 wt % of aliphatic-aromatic copolyester, wherein the starch contains at least 25 wt % of pea starch relative to the total dry weight of the starch.

[0019] Surprisingly, it has been shown that films produced from the polymer composition of the invention have particularly high tensile strength, tear elongation, tear propagation resistance and particularly high dart drop values. Tensile strength is a measure of the strength of the film and refers to the maximum mechanical tensile stress that the material can withstand. It is therefore an important indicator of the mechanical load that a film, for example as a material in a transport bag, can withstand. Tear elongation is a measure of the elasticity of a material. It indicates the elongation that exists at the moment of fracture. The tear elongation is expressed in % relative to the initial length before elongation. Tear propagation resistance refers to the property of a material that it will not tear further even if it is notched. Therefore, a high tear propagation resistance is important, so that, for example, in the case of point damage by sharp objects during transportation, the transport bag will not tear further. The dart drop value is a measure of the puncture resistance of a material. It refers to the weight of the falling weight that pierces the film in 50% of the drop tests. Therefore, a high dart drop value is important, so that the film will not be pierced under mechanical load, for example by heavy objects in a transport bag. Due to these mechanical properties, the films produced from the composition of the invention are particularly suitable for garbage bags and transport bags. Furthermore, the polymer composition according to the present invention is preferably at least partly bio-based and biodegradable.

[0020] Without being bound by a scientific theory, the advantageous properties of the polymer composition according to the invention appear to be attributable to the pea starch content in the polymer composition. In particular, the amylose / amylopectin ratio, molecular weight and / or molecular fine structure of pea starch appear to be decisive compared to other starches, such as potato starch.

[0021] Experiments have shown that polymer compositions with a starch ratio of 25.5% to 50% by weight based on the total dry weight of the polymer composition provide particularly good mechanical properties and simultaneously have a high bio-based ratio and good biodegradability. Lower starch ratios reduce the bio-based ratio in the polymer composition and reduce biodegradability. Higher starch ratios reduce the processability of the polymer composition and result in films having lower stability and poorer mechanical properties, such as low tensile strength, tear elongation, tear propagation resistance and low dart drop values, in film production. If the starch content is too high, films cannot be produced at all.

[0022] The proportion of 30% to 74.5% by weight of aliphatic-aromatic copolyesters based on the total dry weight of the polymer composition ensures good processability of the polymer composition and good mechanical properties of molded parts, films or fibers, especially blown films, prepared from the polymer composition. In addition, the aliphatic-aromatic copolyesters can be partially or completely bio-based. The aliphatic-aromatic copolyesters also improve the biodegradability of the polymer composition and the molded parts, films and fibers prepared therefrom. In the case where the proportion of aliphatic-aromatic copolyesters in the polymer composition is too high or too low, molded parts, films or fibers with desired mechanical properties cannot be prepared from the polymer composition.

[0023] The term "starch" as used herein also includes starch derivatives. Starch derivatives as used herein refer to modified or functionalized starches. As starch derivatives, starches whose free OH groups are at least partially substituted are preferably used. For example, starches modified with ether and / or ester groups can be considered. Other examples of suitable starch derivatives are hydrophobized or hydrophilized starches, in particular hydroxypropyl starch or carboxymethyl starch. Starch can be obtained, for example, from potatoes, corn, cassava or rice. Preferably, native starch, i.e. unmodified or non-functionalized starch, is used for the preparation of the polymer composition of the invention.

[0024] The term "total dry weight" herein refers to the total weight of each component or composition without water. This means that the water content in the corresponding starch is not taken into account when specifying the total dry weight and the corresponding weight ratio. In a mixture consisting of 50g of "wet" pea starch and 50g of aliphatic-aromatic copolyesters with a water content of 10% by weight based on the total weight of pea starch, it corresponds to 45g of pea starch dry weight and 95g of the total dry weight of the mixture. Therefore, the ratio of pea starch relative to the total dry weight of the mixture is equal to 45 divided by 95, i.e. 47.4% by weight in this case. This regulation makes it easier to compare different starches with different water contents and in process steps, such as the starch content after drying or extrusion.

[0025] The term "pea starch" herein refers to starch obtained from peas, regardless of the previously performed process steps. Peas herein refer to the plant genus Pisum. Thus, pea starch may come from any plant species of this plant genus as well as any variants and covariants. For example, garden peas, field peas, smooth peas (Palerbsen), wrinkled peas (Markerbsen) and sugar peas. The pea starch used to prepare the polymer composition of the present invention can contain, for example, 8 to 12% by weight of residual moisture based on the total weight of the pea starch. Preferably, native pea starch, i.e. unmodified or non-functionalized pea starch, is used for preparing the polymer composition of the present invention.

[0026] The term "aliphatic-aromatic copolyester" herein refers to a polyester, i.e. a polymer having a plurality of ester functional groups -(COO)- in its main chain, which consists of at least two different monomer units, at least one of which is an aliphatic hydrocarbon and at least one of which is an aromatic hydrocarbon. When "aliphatic-aromatic copolyester" is mentioned herein, mixtures of different aliphatic-aromatic copolyesters are therefore also included.

[0027] Preferably, the polymer composition comprises a water content of 0.01 wt % to 5 wt %, particularly 0.03 wt % to 3 wt %, 0.04 wt % to 1.5 wt % or 0.05 wt % to 1 wt %, based on the gross weight of the polymer composition, respectively. The water content affects the performance of the molded parts, films or fibers prepared by the polymer composition. The water content also directly affects the processing properties of the polymer composition. If the water content is too low, there is a risk that the components of the polymer composition burn when heated. If the water content is too high, molded parts, films and fibers with desired mechanical properties cannot be produced by the polymer composition, and undesirable foaming may occur particularly in the further processing process.

[0028] According to a preferred embodiment of the polymer composition according to the invention, the starch contains at least 30% by weight, in particular at least 40% by weight, at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, at least 95% by weight, at least 97% by weight, or at least 99% by weight of pea starch, based on the total dry weight of the starch. Such a proportion of pea starch in the starch ensures that the film produced from the polymer composition has particularly good mechanical properties, such as high tensile strength, tear elongation, tear propagation resistance and high dart drop value.

[0029] According to another preferred embodiment of polymer composition of the present invention, starch exists in a deconstructed form. Preferably, in the process of preparing polymer composition by native starch, the deconstructed starch contained in polymer composition of the present invention is formed by mechanical and / or thermal deconstruction. Deconstruction refers to that the granular crystalline structure of native starch is completely or at least mostly destroyed. This is easy to find when observing the diaphragm cross section in a scanning electron microscope, for example. Alternatively, the starch phase of the polymer composition can be separated, and the presence of crystalline components can be checked under a polarizing microscope.

[0030] Within the meaning of the present invention, destructured starch is distinguished from the situation in which native starch is used merely as filler and the granular structure of the starch is at least partially retained.

[0031] The deconstructed starch can advantageously be present in the polymer composition according to the invention in the form of a (possibly preformed) thermoplastic starch (TPS) containing a plasticizer. Plasticizers that come into consideration are carbon-containing plasticizers, such as glycerol and / or sorbitol. However, the deconstructed starch in the polymer composition according to the invention is preferably free of plasticizers as far as possible.

[0032] In order to obtain deconstructed starch even without adding carbonaceous plasticizers, the native starch is preferably homogenized with at least one hydrophobic polymer and at a sufficiently high water content under the action of high shear forces and temperature. The water is preferably completely or preferably partially removed during the homogenization or again by drying at the end of the homogenization. For example, the preparation of such deconstructed starch without plasticizer in a polymer blend with aliphatic-aromatic copolyesters is described in document EP 0596437B1.

[0033] Preferably, the polymer composition according to the invention can comprise 27% to 45% by weight, in particular 28.5% to 40% by weight, or 30% to 35% by weight of starch, based on the total dry weight of the polymer composition, respectively. Such a starch ratio ensures particularly good mechanical properties, while ensuring a high bio-based ratio and good biodegradability. Lower starch contents lead to lower bio-based ratios in the polymer composition, while reducing biodegradability. Higher starch contents reduce the processability of the polymer composition and lead to films with low stability and poor mechanical properties, such as low tensile strength, tear elongation and tear propagation resistance and low dart drop values, in film production. If the starch content is too high, films cannot be produced at all.

[0034] For the polymer composition of the invention, in particular aliphatic-aromatic copolyesters are suitable which are biodegradable according to EN 13432 and / or have a glass transition temperature (Tg) of less than 0° C., in particular less than -4° C., more preferably less than -10° C., further preferably less than -20° C. and most preferably less than -30° C. The aliphatic-aromatic copolyesters contained in the polymer composition of the invention are also preferably thermoplastic.

[0035] According to a preferred embodiment of the polymer composition of the present invention, the aliphatic-aromatic copolyester is a copolyester based on at least one aliphatic dicarboxylic acid having 7 to 22 carbon atoms, an aromatic dicarboxylic acid having 8 to 20 carbon atoms and a diol having 2 to 12 carbon atoms.

[0036] According to a particularly preferred embodiment of the polymer composition according to the invention, the aliphatic-aromatic copolyester is a random copolyester.

[0037] According to another preferred embodiment of the polymer composition according to the invention, the aliphatic-aromatic copolyester is a copolyester based at least on adipic acid and / or sebacic acid, in particular a copolyester based at least on adipic acid.

[0038] According to a particularly preferred embodiment of the polymer composition of the invention, the aliphatic-aromatic copolyester is a copolyester or random copolyester based on 1,4-butanediol, adipic acid and / or sebacic acid and terephthalic acid or a terephthalic acid derivative, in particular dimethyl terephthalate DMT, in particular a random copolyester based on 1,4-butanediol, adipic acid and terephthalic acid or a terephthalic acid derivative, in particular dimethyl terephthalate DMT. It can in particular have a glass transition temperature (Tg) of -25 to -40°C, in particular -30 to -35°C, and / or a melting range of 100 to 120°C, in particular 105 to 115°C. Such an aliphatic-aromatic copolyester ensures that the polymer composition is biodegradable and compostable. In addition, such an aliphatic-aromatic copolyester ensures excellent mechanical properties of molded parts, films or fibers produced from the polymer composition. Such aliphatic-aromatic copolyesters also ensure high tensile strength, tear elongation, tear propagation resistance and high dart drop values ​​in films produced from the polymer composition.

[0039] According to another preferred embodiment of the polymer composition according to the invention, the polymer composition contains 40% to 74.5% by weight, in particular 50% to 74.5% by weight, 55% to 70% by weight, or 60% to 70% by weight of aliphatic-aromatic copolyester, based on the total dry weight of the polymer composition, respectively. Such a content of aliphatic-aromatic copolyester ensures good processability of the polymer composition and leads to good mechanical properties of the molded parts, films or fibers, in particular blown films, prepared from the polymer composition, while having good biodegradability. In the case of too high or too low proportions of aliphatic-aromatic copolyesters in the polymer composition, molded parts, films or fibers with the desired mechanical properties cannot be produced from the polymer composition.

[0040] In addition, the polymer composition according to the invention may contain 0.1 to 5 wt %, in particular 0.2 to 2 wt %, or 0.3 to 1 wt %, of a processing aid, in particular sorbitan monostearate, based on the total dry weight of the polymer composition, respectively. Such processing aids facilitate further processing of the polymer composition, for example blown film extrusion for the preparation of blown films.

[0041] Preferably, the polymer composition according to the invention comprises less than 5 wt.-%, in particular less than 3 wt.-% or less than 1 wt.-%, based on the total dry weight of the polymer composition, of carbon-containing plasticizers, in particular glycerol or sorbitol. Other examples of carbon-containing plasticizers are arabinose, lycose, xylose, glucose, fructose, mannose, allose, altrose, galactose, gulose, idose, inositol, sorbitol, talitol and their monoethoxylated, monopropoxylated and monoacetate derivatives, as well as ethylene, ethylene glycol, propylene glycol, ethylene diglycol, propylene diglycol, ethylene triglycol, propylene triglycol, polyethylene glycol, polypropylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-, 1,3-, 1,4-butanediol, 1,5-pentanediol, 1,6-, 1,5-hexanediol, 1,2,6-, 1,3,5-hexanetriol, neopentyl glycol, trimethylolpropane, pentaerythritol, sorbitol and its acetate, ethoxylated and propoxylated derivatives. Further preferably, the polymer composition of the present invention does not contain carbon-containing plasticizers.Although the polymer composition of the present invention preferably does not contain carbon-containing plasticizers, it has good processing properties and is also particularly suitable for the production of elastic products, such as films.

[0042] The polymer composition according to the invention further preferably contains less than 10% by weight of low molecular weight substances based on the total weight of the polymer composition and is therefore substantially free of plasticizers. Low molecular weight substances in the sense of the present invention are substances with a molecular weight of less than 500 g / mol, in particular less than 250 g / mol. Low molecular weight substances in the sense of the present invention are in particular water, glycerol, sorbitol and / or mixtures thereof.

[0043] The polymer composition according to the invention may also comprise further components, in particular further polymers and / or customary additives, such as processing aids, stabilizers, flame retardants, antiblocking agents and / or fillers.

[0044] According to another preferred embodiment of the polymer composition according to the invention, the polymer composition is biodegradable, in particular completely biodegradable, according to EN 13432. Thus, when the polymer composition according to the invention or products produced therefrom, such as transport bags or garbage bags, enter the natural environment, harm to the animal and plant world can be prevented.

[0045] According to another preferred embodiment of the present invention, the polymer composition of the present invention has thermoplastic properties. Preferably, the polymer composition is thermoplastically processable.

[0046] The present invention also provides a method, by which the above polymer composition can be obtained.

[0047] The method according to the present invention basically comprises the following steps, wherein the individual steps can be performed simultaneously or successively in any order and number of times:

[0048] (i) preparing a mixture by mixing at least the following, each based on the total dry weight of the mixture:

[0049] a) 25.5% to 50% by weight of starch,

[0050] b) 30% to 74.5% by weight of aliphatic-aromatic copolyesters,

[0051] wherein the starch comprises at least 25% by weight of pea starch based on the total dry weight of the starch;

[0052] (ii) homogenizing the mixture by supplying thermal energy and / or mechanical energy;

[0053] (iii) adjusting the water content of the mixture so that the water content of the final product is less than 5% by weight based on the total weight of the mixture.

[0054] Preferably, the method steps are performed in the order described above.

[0055] The above contents about the polymer composition of the present invention are similarly applicable to the aliphatic-aromatic copolyester. The above amounts contained in the polymer composition of the present invention, respectively based on the total dry weight of the polymer composition, are similarly applicable to the amounts used to prepare the mixture, respectively based on the total dry weight of the mixture. The above contents about the polymer composition of the present invention are similarly applicable to the proportion of pea starch based on the total dry weight of starch.

[0056] According to the method of the present invention, the mixture is homogenized. Homogenization can be carried out by any measures familiar to experts in the field of plastic technology. Preferably, the mixture is homogenized by dispersing, stirring, kneading and / or extruding. According to a preferred embodiment of the present invention, shear forces act on the mixture during homogenization. The preparation method suitable for thermoplastic polymers containing starch, which can also be used to prepare the polymer material of the present invention in a similar manner, is described in the document EP 0596437B1 EP, for example. Thus, a uniform homogenization of the mixture is ensured.

[0057] According to a preferred embodiment of the invention, the mixture is heated during homogenization (e.g. in an extruder). According to another preferred embodiment of the invention, the mixture is heated to a temperature of 90 to 250° C., in particular 130 to 220° C., during homogenization or extrusion.

[0058] According to another preferred embodiment of the process according to the invention, the water content of the mixture is adjusted to less than 3% by weight, in particular less than 1.5% by weight, or less than 1% by weight, based on the total weight of the mixture. The water content of the polymer composition is preferably kept at a low level to achieve good reprocessability.

[0059] The water content specified here may relate to the material leaving the extruder. To determine the water content, a sample of the molten extrudate at the nozzle outlet is collected in a sealable container as it leaves the extruder and is sealed airtight. In this regard, care must be taken that the container is filled as completely as possible with the extrudate, so that entrained air in the container is kept as low as possible. After cooling the closed container, it is opened, a sample is taken and the water content is determined by Karl Fischer titration.

[0060] According to a preferred embodiment of the process according to the invention, the water content of the mixture is adjusted by degassing the mixture, in particular by degassing the melt, and / or by drying the mixture during homogenization or extrusion. Energy and costs are thereby saved, since no further process steps are required to adjust the water content.

[0061] The subject of the invention also relates to a polymer composition obtainable according to the process of the invention. Such a polymer composition is particularly suitable for producing films having particularly high tensile strength, tear elongation, tear propagation resistance and particularly high dart drop values. Due to these mechanical properties, films produced from such a composition, in particular blown films, are particularly suitable for use in garbage bags and transport bags. Furthermore, the polymer composition obtained according to the process of the invention is at least partially bio-based and biodegradable.

[0062] The subject of the invention also relates to the use of a polymer composition according to the invention or a polymer composition obtainable by a process according to the invention for producing shaped parts, films or fibers, in particular by blown film extrusion, flat film extrusion or injection molding, in particular for producing films by blown film extrusion. This use allows the production of shaped parts, films or fibers having particularly good mechanical properties, which are at least partially bio-based and biodegradable. In particular, this use allows the production of films having high tensile strength, tear elongation, tear propagation resistance and high dart drop values.

[0063] The subject of the present invention finally also relates to molded parts, films or fibers comprising a polymer composition according to the invention or a polymer composition obtainable by the method according to the invention. These molded parts, films or fibers have particularly good mechanical properties and are at least partially bio-based and biodegradable. The film according to the invention can be a blown film, a flat film or an injection-molded film. The preferred film thickness of the blown film according to the invention is 10 to 100 μm, the preferred film thickness of the flat film according to the invention is 150 to 500 μm, and the preferred film thickness of the injection-molded film according to the invention is 10 to 500 μm. These films, in particular blown films, have high tensile strength, tear elongation, tear propagation resistance and high dart drop values. This makes them particularly suitable for the preparation of transport bags and garbage bags. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] With reference to the five accompanying drawings ( Figures 1 to 5 ) The principles of the present invention are further explained according to embodiments which do not limit the subject matter of the present invention.

[0065] Figure 1 A comparison of the tensile strength of a blown film made from a polymer composition containing pea starch (Film A), a blown film made from a polymer composition containing pea starch and potato starch (Film B), and a blown film made from a polymer composition C containing potato starch (Film C) in the machine direction and transverse direction and at the seam in the machine direction is shown.

[0066] Figure 2Shown is a comparison of the tear elongation at seam in the machine direction and transverse direction for a blown film made from a polymer composition containing pea starch (Film A), a blown film made from a polymer composition containing pea starch and potato starch (Film B), and a blown film made from a polymer composition C containing potato starch (Film C).

[0067] Figure 3 Shown is a comparison of the tear propagation resistance in the machine direction and the cross direction of a blown film prepared from a polymer composition containing pea starch (Film A), a blown film prepared from a polymer composition containing pea starch and potato starch (Film B), and a blown film prepared from a polymer composition C containing potato starch (Film C).

[0068] Figure 4 Shown is a comparison of the unit dart drop value (spez. Dart Drop) of a blown film prepared from a polymer composition containing pea starch (Film A), a blown film prepared from a polymer composition containing pea starch and potato starch (Film B), and a blown film prepared from a polymer composition C containing potato starch (Film C).

[0069] Figure 5 Shown is a comparison of the Dart Drop values ​​(Dart Drop) of a blown film prepared from a polymer composition containing pea starch (Film A), a blown film prepared from a polymer composition containing pea starch and potato starch (Film B), and a blown film prepared from a polymer composition C containing potato starch (Film C). DETAILED DESCRIPTION

[0070] The following materials were used in the comparative examples and examples: poly(butylene adipate-co-terephthalate), PBAT (ECOFLEX F Blend 1201, BASF); native pea starch; native potato starch Sorbitan monostearate (Atmer 103, Croda).

[0071] The properties of the produced films were determined according to the following standards. The film thickness was determined according to standard DIN EN ISO 2286-3:1998. The tensile strength was determined according to standard EN ISO 527. The tear elongation was determined according to standard EN ISO 527. The tear propagation resistance was determined according to standard EN ISO 6383. The dart drop test was carried out according to standard ASTM D 1709. The unit dart drop value was determined by dividing the dart drop value by the film thickness at the thinnest point of the film.

[0072] Example 1 (Preparation of polymer composition)

[0073] The following formulations A, B and C were compounded by Werner & Pfleiderer (COPERION) ZSK 40 twin-screw extruder (synchronous), screw diameter 40 mm, L / D = 42. The data are respectively given as addition ratios in mass percentage, based on the total weight of the formulation (not the total dry weight). Formulation C is used here as a comparative example.

[0074] Table 1: Recipe

[0075] A B C PBAT 68 65 65 Pea starch 31.4 17.3 - Potato starch - 17.3 34.6 Sorbitan monostearate 0.6 0.4 0.4

[0076] The following mixing parameters apply for this:

[0077] Table 2: Temperature curve of zone (Z) of ZSK40 (in °C)

[0078] Z1 Z2 Z3 Z4 Z5 Z6 Z7 Z8 Z9 Z10 Z11 Z12 0 190 190 190 190 170 160 160 160 150 140 0

[0079] Speed: 200min -1

[0080] Throughput: 40kg / h

[0081] Example 2 (Production of Blown Film)

[0082] The polymer compositions A, B and C of Example 1 were melted and further processed into blown films using a COLLIN 30 single-screw extruder (DR. COLLIN, screw diameter 30 mm, L / D=33).

[0083] The following machining parameters are set for this:

[0084] Blast: 39-40%

[0085] Flat fold width of film hose: 325mm

[0086] Throughput: 161g / min

[0087] Foaming ratio: 3.44

[0088] Material temperature: 176℃

[0089] Material pressure: 198bar(A), 167bar(B), 190bar(C)

[0090] Speed: 59mim -1

[0091] Example 3 (Mechanical properties of films)

[0092] The mechanical properties of the films prepared from polymer compositions A, B and C (Film A, Film B and Film C) were measured at room temperature and ambient atmosphere as follows:

[0093] Table 4: Mechanical properties of the films

[0094]

[0095] The films prepared from polymer compositions A, B and C had similar film thicknesses.

[0096] Shockingly and surprisingly, the tensile strength of the films containing pea starch (A and B) in all three directions (longitudinal, transverse and longitudinal seam) was significantly higher than that of the film without pea starch (C) ( Figure 1 ). In the longitudinal and transverse directions, the tensile strength of film A, which contained only pea starch as the starch content, was the highest. In the longitudinal seam, the tensile strength of film B, which contained a mixture of pea starch and potato starch, was the highest.

[0097] When comparing the tear elongation of films A, B, and C, no significant trend was observed ( Figure 2 ). The deviations are within the normal dispersion of the method used (±10%).

[0098] It is worth noting that the tear propagation resistance of films A and B containing pea starch in the longitudinal and transverse directions is significantly higher than that of film C without pea starch ( Figure 3 ). Film B, which contains both pea starch and potato starch, has a particularly high tear propagation resistance.

[0099] Compared to films B and C, film A, which contains only pea starch as starch content, has a particularly high unit dart drop value ( Figure 4 ) and the dart value ( Figure 5 ).

[0100] Surprisingly, the inclusion of pea starch in the polymer composition leads to improved mechanical properties, in particular improved tensile strength, tear propagation resistance and improved dart drop value of blown films made from the polymer composition.

Claims

1. A polymer composition comprising at least the following components, each based on the total dry weight of the polymer composition: a) 25.5% to 50% by weight of starch, b) 30% to 74.5% by weight of aliphatic-aromatic copolyesters, It is characterized in that The starch comprises at least 25 wt% pea starch based on the total dry weight of the starch.

2. The polymer composition according to claim 1, characterized in that The polymer composition comprises a water content of 0.01 wt % to 5 wt % based on the total weight of the polymer composition.

3. The polymer composition according to claim 2, characterized in that The polymer composition comprises a water content of 0.03 wt % to 3 wt % based on the total weight of the polymer composition.

4. The polymer composition according to claim 2, characterized in that The polymer composition comprises a water content of 0.04 wt % to 1.5 wt % based on the total weight of the polymer composition.

5. The polymer composition according to claim 2, characterized in that The polymer composition comprises a water content of 0.05 wt % to 1 wt % based on the total weight of the polymer composition.

6. The polymer composition according to claim 1 or 2, characterized in that The starch contains at least 30% by weight pea starch, based on the total dry weight of the starch.

7. The polymer composition according to claim 6, characterized in that The starch contains at least 40% by weight pea starch, based on the total dry weight of the starch.

8. The polymer composition according to claim 6, characterized in that The starch contains at least 50% by weight pea starch, based on the total dry weight of the starch.

9. The polymer composition according to claim 6, characterized in that The starch contains at least 60% by weight pea starch, based on the total dry weight of the starch.

10. The polymer composition according to claim 6, characterized in that The starch contains at least 70% by weight pea starch, based on the total dry weight of the starch.

11. The polymer composition according to claim 6, characterized in that The starch contains at least 80% by weight pea starch, based on the total dry weight of the starch.

12. The polymer composition according to claim 6, characterized in that The starch contains at least 90% by weight pea starch, based on the total dry weight of the starch.

13. The polymer composition according to claim 6, characterized in that The starch contains at least 95% by weight pea starch, based on the total dry weight of the starch.

14. The polymer composition according to claim 6, characterized in that The starch contains at least 97% by weight pea starch, based on the total dry weight of the starch.

15. The polymer composition according to claim 6, characterized in that The starch contains at least 99% by weight pea starch, based on the total dry weight of the starch.

16. The polymer composition according to claim 1, characterized in that The starch is present in the polymer composition in a destructured form.

17. The polymer composition according to claim 1, characterized in that The polymer composition comprises 27 to 45 wt% starch, based on the total dry weight of the polymer composition.

18. The polymer composition according to claim 17, characterized in that The polymer composition comprises 28.5 to 40 wt% starch, based on the total dry weight of the polymer composition.

19. The polymer composition according to claim 17, characterized in that The polymer composition comprises 30 to 35 wt% starch, based on the total dry weight of the polymer composition.

20. The polymer composition according to claim 1, characterized in that The aliphatic-aromatic copolyester is a copolyester based on at least one aliphatic dicarboxylic acid having 7 to 22 carbon atoms, an aromatic dicarboxylic acid having 8 to 20 carbon atoms and a diol having 2 to 12 carbon atoms.

21. The polymer composition according to claim 1, characterized in that The aliphatic-aromatic copolyester is a random copolyester.

22. The polymer composition according to claim 1, characterized in that The aliphatic-aromatic copolyesters are copolyesters based on at least adipic acid and / or sebacic acid.

23. The polymer composition according to claim 22, characterized in that The aliphatic-aromatic copolyester is a copolyester based at least on adipic acid.

24. The polymer composition according to claim 1, characterized in that The aliphatic-aromatic copolyesters are random copolyesters based on 1,4-butanediol, adipic acid and / or sebacic acid and terephthalic acid or terephthalic acid derivatives.

25. The polymer composition according to claim 24, characterized in that The aliphatic-aromatic copolyester is a random copolyester based on 1,4-butanediol, adipic acid and terephthalic acid or a terephthalic acid derivative.

26. The polymer composition according to claim 24 or 25, characterized in that The terephthalic acid derivative is dimethyl terephthalate (DMT).

27. The polymer composition according to claim 1, characterized in that The polymer composition contains 40 wt% to 74.5 wt% of the aliphatic-aromatic copolyester, based on the total dry weight of the polymer composition.

28. The polymer composition according to claim 27, characterized in that The polymer composition contains 50 wt% to 74.5 wt% of the aliphatic-aromatic copolyester, based on the total dry weight of the polymer composition.

29. The polymer composition according to claim 27, characterized in that The polymer composition contains 55 to 70 weight percent of the aliphatic-aromatic copolyester, based on the total dry weight of the polymer composition.

30. The polymer composition according to claim 27, characterized in that The polymer composition contains 60 to 70 weight percent of the aliphatic-aromatic copolyester, based on the total dry weight of the polymer composition.

31. The polymer composition according to claim 1, characterized in that The polymer composition contains 0.1 wt % to 5 wt % of the processing aid, based on the total dry weight of the polymer composition.

32. The polymer composition according to claim 31, characterized in that The polymer composition contains 0.2 wt % to 2 wt % of the processing aid, based on the total dry weight of the polymer composition.

33. The polymer composition according to claim 31, characterized in that The polymer composition contains 0.3 wt % to 1 wt % of the processing aid, based on the total dry weight of the polymer composition.

34. The polymer composition according to any one of claims 31 to 33, characterized in that The processing aid is sorbitan monostearate.

35. The polymer composition according to claim 1, characterized in that The polymer composition comprises less than 5 wt% of a carbon-containing plasticizer, based on the total dry weight of the polymer composition.

36. The polymer composition according to claim 35, characterized in that The polymer composition comprises less than 3 wt% of a carbon-containing plasticizer, based on the total dry weight of the polymer composition.

37. The polymer composition according to claim 35, characterized in that The polymer composition comprises less than 1 wt% of a carbon-containing plasticizer, based on the total dry weight of the polymer composition.

38. The polymer composition according to any one of claims 35 to 37, characterized in that The carbon-containing plasticizer is glycerol or sorbitol.

39. The polymer composition according to claim 35, characterized in that Alternatively, the polymer composition does not contain a carbon-containing plasticizer.

40. The polymer composition according to claim 1, characterized in that The polymer composition is biodegradable according to EN 13432.

41. The polymer composition according to claim 40, characterized in that The polymer composition is fully biodegradable according to EN 13432.

42. A method for producing a polymer composition according to any one of claims 1 to 41, characterized in that The following steps are involved: (i) producing a mixture by mixing at least the following, each based on the total dry weight of the mixture: a) 25.5% to 50% by weight of starch, b) 30% to 74.5% by weight of aliphatic-aromatic copolyesters, wherein the starch comprises at least 25% by weight of pea starch based on the total dry weight of the starch; (ii) homogenizing the mixture by supplying thermal energy and / or mechanical energy; (iii) adjusting the water content of the mixture so that the water content of the final product is less than 5% by weight based on the total weight of the mixture.

43. The method according to claim 42, characterized in that The mixture is homogenized by dispersion, the action of shear forces on the mixture, stirring, kneading and / or extrusion.

44. The method according to claim 42 or 43, characterized in that The mixture is heated to a temperature of 90 to 250° C. during homogenization or extrusion.

45. The method according to claim 44, characterized in that The mixture is heated to a temperature of 130 to 220° C. during homogenization or extrusion.

46. ​​The method according to claim 42, characterized in that The water content of the mixture is adjusted to less than 3% by weight, based on the total weight of the mixture.

47. The method according to claim 46, characterized in that The water content of the mixture is adjusted to less than 1.5% by weight, based on the total weight of the mixture.

48. The method according to claim 46, characterized in that The water content of the mixture is adjusted to less than 1% by weight, based on the total weight of the mixture.

49. The method according to claim 42, characterized in that The water content of the mixture was adjusted during the homogenization process.

50. The method of claim 42, wherein: The water content of the mixture is adjusted by degassing the mixture and / or by drying the mixture during homogenization or extrusion.

51. The method according to claim 50, characterized in that The water content of the mixture was adjusted by degassing the melt.

52. A polymer composition obtainable by the process according to any one of claims 42 to 51.

53. Use of a polymer composition according to any one of claims 1 to 41 or claim 52 for the preparation of shaped articles, films or fibers.

54. The use according to claim 53, characterized in that For the production of shaped parts, films or fibers by blown film extrusion, flat film extrusion or injection molding.

55. The use according to claim 53, characterized in that For the production of thin films by blown film extrusion.

56. A molded article, film or fiber comprising the polymer composition according to any one of claims 1 to 41 or claim 52.